2012
DOI: 10.1111/cpr.12003
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation of fibroblasts and endothelial cells is enhanced by treatment with Phyllocaulis boraceiensis mucus

Abstract: Previously, mucus of some molluscs has been studied as a potential source of new natural compounds capable of inducing cell proliferation and of remodelling tissue. Here, the focus of the study is possible use of mucus released by Phyllocaulis boraceiensis - a compound inducing cell proliferation and enhancing collagen synthesis in dermal fibroblasts and inducing proliferation human endothelial cell cultures. Fibroblasts treated with P. boraceiensis mucus at concentrations below 0.012 μg/μl developed high rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Neonatal foreskin dermal fibroblasts (PCS-201-010; denoted as “Foreskin FB 1” in the text) [27,28] and embryonic lung fibroblasts (IMR-90; denoted as “Lung FB” in the text) [29] were obtained from American Type Culture Collection (ATCC) and cultured according to protocols recommended by ATCC. A second strain of neonatal foreskin dermal fibroblasts (AH1F; denoted as “Foreskin FB 2” in the text) [30] was derived originally by Dr. Lynn Allen-Hoffmann at the University of Wisconsin [31].…”
Section: Methodsmentioning
confidence: 99%
“…Neonatal foreskin dermal fibroblasts (PCS-201-010; denoted as “Foreskin FB 1” in the text) [27,28] and embryonic lung fibroblasts (IMR-90; denoted as “Lung FB” in the text) [29] were obtained from American Type Culture Collection (ATCC) and cultured according to protocols recommended by ATCC. A second strain of neonatal foreskin dermal fibroblasts (AH1F; denoted as “Foreskin FB 2” in the text) [30] was derived originally by Dr. Lynn Allen-Hoffmann at the University of Wisconsin [31].…”
Section: Methodsmentioning
confidence: 99%
“…Also, the production and secretion of ECM components and collagen type I fibers was enhanced after 24 h of treatment, revealing a biphasic dose response, a proliferative low dose, and a toxic high dose. These results demonstrate that the treatment with P. boraceiensis mucus produces pronounced changes in fibroblast cell number and morphology and in the amount of well-ordered collagen deposition [15]. This same product was used in essays of cicatrization, and it was shown that mice subjected to a dorsal incision and treated daily with a ointment composed of P. boraceiensis mucus demonstrated a more efficient healing process and wound closure after application of 0.012 lgÁlL À1 P. boraceiensis mucus [16].…”
Section: Introductionmentioning
confidence: 70%
“…Proliferation of endothelial cells and fibroblasts was observed from 48 h after treatment with P. boraceiensis mucus, showing that this compound acts as an inducer of proliferation, suggesting that, once it has induced an increase in cell proliferation, all correlated factors will increase, as shown by the results reported here. The authors also present images of endothelial cell cultures treated with P. boraceiensis mucus forming blood vessels, which is clear evidence of angiogenesis .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…2c shows that trypsinized HDFn cells had limited attachment to the culture dish. However, when delivered by using the FN-SUV system, the number of active broblasts (seen as spindle-shaped cells with long lamellipodia) increased signi cantly 25 . A quantitative comparison of cell attachment among the experimental groups was performed by calculating the total area of attached cells, as shown in Fig.…”
Section: Mainmentioning
confidence: 99%